Accounting theory: perceptions on the characteristics of the discipline and the impact of resolution CNE/CES No. 1/2024 on higher education institutions (HEIs) in Pernambuco - Lira, Ávila Kézia Menezes; Leitão, Carla Renata Silva (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To analyze the perception of coordinators and professors of undergraduate accounting courses at higher education institutions in Pernambuco regarding the characteristics of the Accounting Theory discipline and the effects of Resolution CNE/CES No. 1/2024. Methodology: This study employed a descriptive research design with a quantitative approach and a survey-type outline. It was conducted with 96 public and private Higher Education Institutions (HEIs) in Pernambuco that offer accounting programs. Data were collected through a questionnaire and analyzed using descriptive statistics. The research investigated the characteristics of the Accounting Theory course and the potential impacts of Resolution CNE/CES No. 1/2024. Results: The survey of 17 HEIs in Pernambuco revealed that the majority offer the Accounting Theory course as a mandatory subject, with a predominant workload of 60 hours and no standardization regarding the semester in which it is offered. Most institutions do not require prerequisites, and the most widely used textbooks are those by Hendriksen & Van Breda and Iudícibus. The HEIs are aware of the new Resolution CNE/CES No. 001/2024 and have already begun making adjustments. Despite potential changes, all institutions consider the course to be important for accounting education. Contributions of the Study: This study broadened the analysis of the Accounting Theory course to include all Higher Education Institutions in Pernambuco, encompassing both public and private HEIs. It presented updated data on the course's offering, workload, bibliography, and prerequisites. The research highlighted a significant divergence: most HEIs in Pernambuco do not require prerequisites for the course, unlike what has been identified in public universities in the Northeast region. Another relevant contribution is the analysis of the impact of the new Resolution CNE/CES No. 001/2024, showing that many institutions are already in the process of adapting to the new curricular guidelines and recognize the need to align the course with the competencies expected of graduates.